1995
DOI: 10.1159/000201253
|View full text |Cite
|
Sign up to set email alerts
|

Activated Immunocompetent Cells in Rat Colitis Mucosa Induced by Dextran Sulfate Sodium and Not Complete but Partial Suppression of Colitis by FK506

Abstract: Administration of dextran sulfate sodium (DSS) solutions to rats induced colitis which resembled mucosal lesions of human ulcerative colitis. Recent reports have shown that some cytokines are related to the pathogenesis of ulcerative colitis. In the present report, we describe the production of two cytokines in colitis mucosa in this DSS model. Using a cytotoxicity assay and a radioimmunoassay, we observed significant increases in levels of tumor necrosis factor-α (TNF-α) in the colitis mucosa and detected int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 7 publications
3
32
0
Order By: Relevance
“…MPO activity is a useful index for evaluating neutrophil infiltration in colonic tissues after induction of colitis (Takizawa et al, 1995). Using a standard enzymatic procedure, we observed that MPO levels in the colon tissue of vehicle-treated DSS mice were 3.3-fold greater than those in the colon tissue of control healthy mice (p ϭ 0.001) (Fig.…”
Section: As605240 Treatment Extends Lifespan In a Mouse Model Of Dss-mentioning
confidence: 89%
“…MPO activity is a useful index for evaluating neutrophil infiltration in colonic tissues after induction of colitis (Takizawa et al, 1995). Using a standard enzymatic procedure, we observed that MPO levels in the colon tissue of vehicle-treated DSS mice were 3.3-fold greater than those in the colon tissue of control healthy mice (p ϭ 0.001) (Fig.…”
Section: As605240 Treatment Extends Lifespan In a Mouse Model Of Dss-mentioning
confidence: 89%
“…Although disease can be induced by acute administration of DSS in severe combined immunodeficient mice (48), other studies provide evidence that cyclosporin and FK506 are protective in the short-term acute DSS model, suggesting that T cells participate in disease development (49,50). Furthermore, specific T cell subsets exert protective effects after acute administration of DSS (51).…”
Section: Discussionmentioning
confidence: 99%
“…To allow inference of pharmacological effect from occult blood discharge, occult blood level and number of days from first drug administration were used to establish an occult blood index, which was calculated thus: occult blood index ¼ Culture of colonic mucosa DSS-induced colitis rats treated for 6 days with IgG were killed on the day after final administration and the colon from the rectum to the sigmoid colon was removed. According to the method of Takizawa et al [18], the colons were cut open and the mucosa gently stripped off. The stripped mucosa was transferred to 15 ml polypropylene tubes (Falcon; Becton Dickinson, Franklin Lakes, NJ), where it was washed in a medium of RPMI 1640 (Flow Labs, Irvine, UK) containing 100 U/ml penicillin and 100 mg/ml streptomycin through a process of centrifugation at 400 g, aspiration of the supernatant and addition of clean RPMI 1640.…”
Section: Calculation Of Occult Blood Indexmentioning
confidence: 99%